2009
DOI: 10.1007/s11126-009-9103-9
|View full text |Cite
|
Sign up to set email alerts
|

Insight, Global Functioning and Psychopathology Amongst In-patient Clients with Schizophrenia

Abstract: To explore whether cognitive impairment and global functioning can predict the degree of insight into illness as well as whether insight is mediated by specific symptom dimensions of psychopathology in schizophrenia. A dimensional/cross sectional approach was used. A mixed group of clients (n = 36) were assessed as part of a routine clinical evaluation. The Wechsler Adult Intelligence Scale (WAIS) was used as a measure of intellectual performance, the Brief Symptom Inventory (BSI) was used as a measure of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
18
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 55 publications
7
18
0
2
Order By: Relevance
“…This study, which does not find a significant relationship between insight and neurocognitive functions, is consistent with other larger studies that have not established a relationship between insight and executive functions, memory, and attention (10,17,18). However, in a recent meta-analysis, a significant but small relation was found between neurocognitive functions and clinical insight (19).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study, which does not find a significant relationship between insight and neurocognitive functions, is consistent with other larger studies that have not established a relationship between insight and executive functions, memory, and attention (10,17,18). However, in a recent meta-analysis, a significant but small relation was found between neurocognitive functions and clinical insight (19).…”
Section: Discussionsupporting
confidence: 89%
“…Past research regarding this model revealed inconsistent findings. In some studies, there was a relationship between poor insight, executive functions (14,15) and memory impairment (16), whereas no relation was found in other studies (17,18). In a recent meta-analysis, neurocognitive impairment has been shown to have a significant but small effect on clinical insight (19).…”
mentioning
confidence: 99%
“…This finding is expected and intuitive as individuals with a higher level of symptoms producing a significant functional impairment have fewer resources to achieve and maintain the real-word milestones. Literature confirmed our results reporting significant relationships between severity of symptom domains and functional outcome in schizophrenia and mood disorders [49][50][51][52][53][54][55][56][57]. The lack of significant relationships between PSP change and severity of global symptoms in BPD patients might depend on the considerable heterogeneity of BPD symptomatology that would produce unstable and unpredictable effects on the real-world functioning.…”
Section: Discussionsupporting
confidence: 87%
“…Impaired insight is linked to important outcome variables such as treatment non-adherence [7][8][9], higher rates of re-hospitalization [10], poorer social skills [11], reduced social relationships [12,13], compromised work performance [14,15], and a longer duration of untreated psychosis [16,17]. Impaired insight has also been linked to concurrent and prospective assessments of quality of life [18], poorer personal recovery [19], and poor global functioning [20,21]. In line with this, other investigations have shown that individuals with higher levels of insight are better able to appraise their level of psychosocial functioning [22] and tend to have more self-efficacy when compared to individuals with poorer insight [23].…”
Section: Introductionmentioning
confidence: 99%